The effects of material’s features and feeding mechanism on high-gain antenna construction - Hamed A. Al-Falahi; Drai Ahmed Smait; Sami Abduljabbar Rashid; Sarmad Nozad Mahmood; Sameer Alani (Institute of Advanced Engineering and Science, 2022)
This study investigates the performance of flexible, wideband antennas with high gain properties. The high gain feature can often be obtained by positioning a reflector in the same planes as the adjacent radiator. For flexibility, this survey discusses the antennas that were printed on the flexible substrate materials. Based on these properties, the antenna can be recognized in a variety of wireless applications, including wireless local-area-network (WLAN), Worldwide Interoperability for microwave access (WI-Max), wireless body area network (WBAN), and radio frequency identification (RFID), as well as wearable applications. The high-gain antennas are compact radio wave-based antennas that provide precise radio transmission management. Such antennas deliver more energy to the receiver, increasing the frequency of the received signal. By gathering more power, high-gain antennas may emit signals quicker. Furthermore, because directional antennas broadcast fewer signals from the main wave, interference may be greatly minimized. Finally, this article identifies the role of lightweight high gain flexible antennas in terms of their size, substrate materials, design, and feeding mechanisms, all of which can affect bandwidth, gain, radiation efficiency, and other important factors.